2011
DOI: 10.1590/s1516-35982011000100008
|View full text |Cite
|
Sign up to set email alerts
|

Morphogenetic and structural characteristics of xaraes palisadegrass submitted to cutting heights

Abstract: The objective of this work was to evaluate the morphogenetic and structural characteristics of xaraes palisadegrass submitted to three cutting heights (15, 20 and 25 cm) when the sward reached 95% of light interception during regrowth. The experiment was carried out according to a complete randomized block design with three replications. The sward surface height under the cutting condition of 95% of light interception was very homogeneous with values around 30 cm. The increase in cutting height reduced the lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
1
14

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 15 publications
2
22
1
14
Order By: Relevance
“…Given that the criterion for termination of regrowth was the same (95% of light interception), the density of basal tillers did not vary between the post-grazing heights or seasons with an average of 374, 356 and 386 of tillers/m 2 for the post-grazing heights of 30, 50 and 50-30 cm, respectively. Sousa et al (2010), evaluating the Andropogon grass and Sousa et al (2011), evaluating the Xaraes palisade grass subjected to different cutting heights, all performed when the canopy reached 95% of light interception, also reported no changes in density of basal tillers, corroborating, thus, the results obtained in this study.…”
Section: Resultssupporting
confidence: 86%
“…Given that the criterion for termination of regrowth was the same (95% of light interception), the density of basal tillers did not vary between the post-grazing heights or seasons with an average of 374, 356 and 386 of tillers/m 2 for the post-grazing heights of 30, 50 and 50-30 cm, respectively. Sousa et al (2010), evaluating the Andropogon grass and Sousa et al (2011), evaluating the Xaraes palisade grass subjected to different cutting heights, all performed when the canopy reached 95% of light interception, also reported no changes in density of basal tillers, corroborating, thus, the results obtained in this study.…”
Section: Resultssupporting
confidence: 86%
“…In Brachiaria brizantha swards, SOUSA et al (2011) showed that higher defoliation severity Table 1 -Leaf senescence (LSR), stem and pseudo stem elongation (SER), and leaf appearance (LAR) rates (cm tiller -1 day -1 ) in elephant grass cv. 'Pioneiro' swards grazed at two pre-grazing heights (cm) and two severities of defoliation (%) during the regrowth stages.…”
Section: Resultsmentioning
confidence: 99%
“…In this experiment, the criterion for determining the beginning of grazing was the same in all treatments, i.e., 95% light interception, which does not characterize a condition of intense competition for light, may justify the absence of differences in leaf appearance rate, phyllochron, leaf lifespan, final leaf length, and leaf senescence rate in all post-grazing heights. Studies based on growth and development rates of the plants when 95% of light interception was used do not show differences between the intensities of defoliation tested for the Andropogon grass (Sousa et al, 2010) and Xaraes palisadegrass (Sousa et al, 2011). This shows that the post-grazing heights adopted were adequate for the guinea grass cv.…”
Section: Discussionmentioning
confidence: 83%
“…The use of morphogenesis to study growth and development of plants in sward allows for a better understanding of dynamics responses of the sward to defoliation (Silveira et al, 2010;Sousa et al, 2010Sousa et al, , 2011. In adequate environmental conditions (photoperiod, temperature, humidity and soil fertility), the plants accelerate their growth rhythm, increasing their leaf appearance and elongation rates (Marcelino et al, 2006) and their stem elongation rate (Mazzanti et al, 1994;Difante et al, 2008).…”
Section: Introductionmentioning
confidence: 99%